Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan (Studi Kasus Karyawan Bagian Pelinting Di KSU PERDULA Ngoro Jombang) - Muhyiddin Lubis (BIMA : Journal of Business and Innovation Management, 2022)
This study aims to determine whether there is an influence between motivation and work environment on employee job satisfaction (a case study in the rolling division at KSU PERDULA Ngoro Jombang). Method used is quantitative research. The number of samples was 92 respondents who were permanent employees at KSU PERDULA Ngoro Jombang using random sampling techniques and uses questionnaire data collection techniques, interviews, documentation and observation. In data analysis using statistical methods using multiple linear regression tests. The results showed: (1) motivation has an effect on job satisfaction of KSU PERDULA Ngoro Jombang employees, (2) The work environment has an effect on employee job satisfaction at KSU PERDULA Ngoro Jombang, (3) motivation and work environment influence job satisfaction. employees at KSU PERDULA Ngoro Jombang. Keywords: Motivation; Work Environment; Employee Job Satisfaction